The relationship between the factor of interest (level of understanding, technology self-efficacy and design) with level of usage of i-learn / Mohamad Firdaus Mohamed Khatib and Mohd Fadhil Ariffin - Mohamed Khatib, Mohamad Firdaus; Ariffin, Mohd Fadhil (2012)
The purpose of this study was to examine the relationship between factor of interests (level of understanding, technology self-efficacy, and design) with level of usage of i-learn among BM232 students in Universiti Teknologi MARA (UiTM), Pahang. The respondents involved in the study were Bachelor in Office Systems Management students only. The major finding indicated that most of the students were engaged in the use of usage of i-Iearn. The present study has identified that there was relationship between the factors of interest (level of understanding, technology self-efficacy, and design) with level of usage of i-learn. Generally from the analysis showed that positive relationship between level of usage and factor of interests was moderate level witch mean was score 0.484**.